Anterior Interdental Papillary Loss among Young Adults of Bhubaneswar: A Cross Sectional Survey - Bhagyashree Lenka1 , Rinkee Mohanty2 , Anurag Satpathy3 , Rashmita Nayak3 , Abhaya Chandra Das4 , So (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Presence of intact interdental papilla is considered as an essential component of health andesthetics. Interdental papilla loss or “black triangles” results in food retention, phonetic problems andunaesthetic appearance especially in maxillary anterior regions but there are very few studies reporting theprevalence of this condition.Aim: To assess the prevalence of anterior interdental papillary loss among young adults in Bhubaneswar.Materials and Method: A total of 483 patients were screened and 157 patients met the inclusion andwere assessed for papilla loss parameters (Norland & Tarnow and Jemt Classification).All these patientsunderwent oral prophylaxis and then clinical photographs were taken.Results: High frequency of papillary loss was seen in males (62.4%) compared to females (37.6%). Papillaryloss was commonly seen in midline (51.0%) than in laterals(49.0%). Jemt Grade 2 (43.3%)and Nordlandand Tarnow Class I(43.3%) papillary recession was more commonly seen.Conclusion: There is higher prevalence of papilla loss in the midline region of maxillary anteriors presentinghalf or more of the height of the papilla